IBN SINA THE SIGNIFICANCE AND STUDY OF THE BALANCE OF BODY, SOUL AND MIND (Academia Science Repository, 2023)
It is known that the concept of a perfect person has a very old history. Our great philosophers and sheikhs have expressed excellent opinions in this regard. In general, the moral education of a person was in the constant focus of our ancestors. In the article, the views and opinions of our great physician ancestor Ibn Sina on the balance of body, soul and mind were researched and suggestions were made.